Feasibility of Learning Media Video Tutorial Bali Bun Modification using Crimping Iron Tools - Ifa Nurhayati; Sita Nurmasitah (Jurnal Penelitian Pendidikan, 2024)
Learning videos are a form of digital media that displays a combination of audio and visual, which aims to convey learning materials such as concepts, principles, procedures, and theories of knowledge. The goal is to facilitate the understanding of learning material for students, so that they can master the material better. This study aims to evaluate the level of effectiveness of learning videos in teaching the process of making shapes. This study used a pre-experimental method with a one-shot case study design. Data were collected through interviews, literature studies, and questionnaire dissemination. The research was conducted at Semarang State University, especially at the Faculty of Engineering, Beauty Education Study Program, in the even semester of the 2022/2023 academic year, involving 74 students from the class of 2022. The results showed that learning videos were considered very feasible in terms of material, with an average score of 3.55, and Highly favourable in terms of media, with an average score of 3.52. Based on these results, it is concluded that learning videos can be effectively applied in teaching material about the process of making modified Balinese buns using Crimping Iron.